The effect of exercise and disease status on mobilization of anti-tumorigenic and pro-tumorigenic immune cells in women with breast cancer - Koivula, Tiia; Lempiäinen, Salla; Neuvonen, Joona; Norha, Jooa; Hollmén, Maija; Sundberg, Carl Johan; Rundqvist, Helene; Minn, Heikki; Rinne, Petteri; Heinonen, Ilkka (Frontiers in Immunology, 2024)
Background Mobilization of certain immune cells may improve the ability of the immune system to combat tumor cells, but the effect of acute exercise on mobilizing immune cells has been sparsely investigated in cancer patients. Therefore, we examined how acute exercise influences circulating immune cells in breast cancer patients. Methods Nineteen newly diagnosed breast cancer patients aged 36-68 performed 30 minutes of moderate-intensity exercise with a cycle ergometer. Blood samples were collected at various time points: at rest, at 15 (E15) and 30 minutes (E30) after onset of the exercise, and at 30 and 60 minutes post-exercise. We analyzed several immune cell subsets using flow cytometry. Results Acute exercise increased the number of total leukocytes, neutrophils, lymphocytes, monocytes, basophils, total T-cells, CD4+ T-cells, T helper (Th) 2-cells, Th 17-cells, CD8+ T-cells, CD4-CD8- T-cells, CD56+ natural killer (NK) cells, and CD14-CD16+ monocytes. Many of the changes were transient and even biphasic. Proportions of NK-cells and CD8+ T-cells increased, while the proportion of myeloid derived suppressor cells (MDSCs) reduced, and proportion of regulatory T-cells remained unchanged by exercise. Several associations were detected between cell mobilizations and disease state. For instance, tumor size correlated negatively with NK cell mobilization at E15, and progesterone receptor positivity correlated negatively with CD8+ T-cell mobilization. Conclusions The findings show that the proportions of CD8+ T-cells and NK cells increased and the proportion of MDSCs proportion decreased in breast cancer patients after 30-minute exercise, suggesting a change in the profile of circulating immune cells towards more cytotoxic/anti-tumorigenic. The mobilization of some immune cells also appears to be related to the disease state.